TINJAUAN YURIDIS TERHADAP PENERAPAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI PUTUSAN NO 46/PID.SUS/ 2019 PENGADILAN NEGERI MAUMERE) - Ndaumanu, Novaldy I; Sinurat, Aksi; Wilhelmus, Bhisa Vitus (Petitum Law Journal, 2024)
The quality of the judge's decision in adjudicating is when the judge is able to hand down a decision by paying attention to three very essential things, namely legal certainty, justice, and expediency. Interpreting the element of "possessing, storing, possessing, or providing" class I narcotics as contained in Article 112 paragraph (1) of the Narcotics Law must also consider the purpose or purpose of the accused. Because the terminology "possess, store, control or provide" provided for by Article 112, cannot be applied strictly following the textual. If this is not done carefully and carefully, it will have an impact on imposing crimes with inappropriate crimes and cause injustice to drug abusers. The results of the research stated that: first, the provisions of Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics do not have clarity in substance, namely in the word "possessing" if in the application there is a mistake in interpreting " possessing" can cause legal injustice, considering the application of article 112 paragraph (1) by the panel of judges in case number 46/ Pid.Sus/ 2019/ Maumere District Court is not appropriate, The application of this article is considered inappropriate because the judges' consideration only pays attention to the fulfillment of criminal elements written in article 112 paragraph (1) of Law No. 35 of 2009 concerning Narcotics. Second, the Maumere court judges ignored the subject's status as an abuser and skewed with the second alternative charge (article 112 paragraph 1), but in a review in accordance with the expectation of the application of article 127 paragraph (1) point a by the Supreme Court.